Tumor-induced metabolic immunosuppression: Mechanisms and therapeutic targets - Jean-Ehrland Ricci (Cell Reports)
Summary: Metabolic reprogramming in both immune and cancer cells plays a crucial role in the antitumor immune response. Recent studies indicate that cancer metabolism not only sustains carcinogenesis and survival via altered signaling but also modulates immune cell function. Metabolic crosstalk within the tumor microenvironment results in nutrient competition and acidosis, thereby hindering immune cell functionality. Interestingly, immune cells also undergo metabolic reprogramming that enables their proliferation, differentiation, and effector functions. This review highlights the regulation of antitumor immune responses through metabolic reprogramming in cancer and immune cells and explores therapeutic strategies that target these metabolic pathways in cancer immunotherapy, including using chimeric antigen receptor (CAR)-T cells. We discuss innovative combinations of immunotherapy, cellular therapies, and metabolic interventions that could optimize the efficacy of existing treatment protocols.